2018
DOI: 10.1097/aog.0000000000002645
|View full text |Cite|
|
Sign up to set email alerts
|

A 17β-Estradiol–Progesterone Oral Capsule for Vasomotor Symptoms in Postmenopausal Women

Abstract: ClinicalTrials.gov, NCT01942668.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 22 publications
7
81
0
Order By: Relevance
“…The primary efficacy and safety endpoints were changes from baseline to weeks 4 and 12 in the frequency and severity of moderate to severe vasomotor symptoms, and the incidence of endometrial hyperplasia at 12 months. The positive results with respect to the two primary endpoints of the trial have already been reported 1 . The REPLENISH trial also investigated additional efficacy endpoints, such as quality of life 2 using the Menopause-Specific Quality of Life questionnaire, a validated questionnaire assessing four domains (vasomotor, psychosocial, physical, sexual), which showed improvement within the first 3 treatment months.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…The primary efficacy and safety endpoints were changes from baseline to weeks 4 and 12 in the frequency and severity of moderate to severe vasomotor symptoms, and the incidence of endometrial hyperplasia at 12 months. The positive results with respect to the two primary endpoints of the trial have already been reported 1 . The REPLENISH trial also investigated additional efficacy endpoints, such as quality of life 2 using the Menopause-Specific Quality of Life questionnaire, a validated questionnaire assessing four domains (vasomotor, psychosocial, physical, sexual), which showed improvement within the first 3 treatment months.…”
mentioning
confidence: 68%
“…Perhaps the most important result of REPLENISH is the demonstration of endometrial safety using progesterone as the progestogen component 1 . This has been the subject of controversial discussion for years.…”
mentioning
confidence: 99%
“…Data from the REPLENISH trial show that, for the most part, the frequency of moderate-to-severe VMS significantly improved from week 3 to 12 for E2/P4 doses of 1 mg/ 100 mg, 0.5 mg/100 mg, and 0.25 mg/50 mg, and at weeks 6-12 for 0.5 mg/50 mg compared with placebo (p < 0.05) 25 . Significant reductions in VMS severity were observed at weeks 3-12 for 1 mg E2/100 mg P4 and 0.5 mg E2/100 mg P4, and at most weeks between 6 and 12 for 0.5 mg E2/50 mg P4 and 0.25 mg E2/50 mg P4 25 .…”
Section: Menopausal Symptomsmentioning
confidence: 97%
“…A preliminary report of the phase-3 REPLENISH trial showed multiple doses of the investigational, oral, continuous combined, solubilized E2/P4 (TX-001HR, TherapeuticsMD, Boca Raton, FL, USA: 1 mg/100 mg, 0.5 mg/100 mg, 0.5 mg/ 50 mg, 0.25 mg/50 mg) resulting in no cases of endometrial hyperplasia or cancer (n ¼ 274-306 per group) after 12 months 25 . This was the first sufficiently powered trial to identify oral P4 doses that antagonized the endometrial effects of different E2 doses (1 mg, 0.5 mg, or 0.25 mg) 25 .…”
Section: Introductionmentioning
confidence: 99%
“…TX-001HR (TherapeuticsMD, Boca Raton, FL, USA) combines 17b-estradiol (E2) and P4 in a single, oral, softgel capsule 25 . The 1 mg E2/100 mg P4 dose was approved by the US Food and Drug Administration (FDA) as Bijuva TM (TherapeuticsMD) 26 for the treatment of moderate to severe VMS in postmenopausal women with a uterus in October 2018, the first, combined E2/P4 oral formulation approved by the FDA.…”
Section: Introductionmentioning
confidence: 99%